Conjuring Asia magic, orientalism, and the making of the modern world - Goto-Jones, Christopher S. (Cambridge University Press, 2016)
The promise of magic has always commanded the human imagination, but the story of industrial modernity is usually seen as a process of disenchantment. Drawing on the writings and performances of the so-called 'Golden Age Magicians' from the turn of the twentieth century, Chris Goto-Jones unveils the ways in which European and North American encounters with (and representations of) Asia - the fabled Mystic East - worked to re-enchant experiences of the modern world. Beginning with a reconceptualization of the meaning of 'modern magic' itself - moving beyond conventional categories of 'real' and 'fake' magic - Goto-Jones' acclaimed book guides us on a magical mystery tour around India, China and Japan, showing us levitations and decapitations, magic duels and bullet catches, goldfish bowls and paper butterflies. In the end, this mesmerizing book reveals Orientalism as a kind of magic in itself, casting a spell over Western culture that leaves it transformed even today